The Perception of Romanian Immigrants in Spain: The Case of the Hola, soy rumano Campaign*. Issue 10 (26th November 2017) - Prieto-Arranz, José Igor; Iacob, Mihai
Abstract: This article discusses Romanian immigration in Spain by focusing on the role the media play in society-making in the light of the three television spots released as part of the multi-media Hola, soy rumano campaign, commissioned by the Romanian Government to improve the image of Romanian immigrants among Spanish nationals. Informed by Gane's reading of Lyotardian theory and Couldry's conception of media reception, the semiotic analysis of the spots will attempt to bring to the fore several possible readings of the texts under scrutiny, which will eventually be crossed with media practices relating to the consumption of the said texts. Results will point to the not very successful, and probably unexpected, impact of the campaign, which will be linked to the complex national identity issues currently in force in Spain, as well as the othering of immigrant communities in the country. The novelty of the present work lies in its interdisciplinary approach to the phenomenon of immigration, and its focus on Romanian immigration in Spain—a country in which, as in Italy, immigration studies are still in their infancy.